Pectoralis and Serratus Fascial Plane Blocks Each Provide Early Analgesic Benefits Following Ambulatory Breast Cancer Surgery: A Retrospective Propensity-Matched Cohort Study. (July 2017) - Abdallah, Faraj W.; MacLean, David; Madjdpour, Caveh; Cil, Tulin; Bhatia, Anuj; Brull, Richard
Abstract : BACKGROUND: Pectoralis and serratus blocks have been described recently for use in breast surgery, but evidence supporting their analgesic benefits is limited. This cohort study evaluates the benefits of adding a pectoralis or serratus block to conventional opioid-based analgesia (control) in patients who underwent ambulatory breast cancer surgery at Women's College Hospital between July 2013 and May 2015. We tested the joint hypothesis that adding a pectoralis or serratus block reduced postoperative in-hospital (predischarge) opioid consumption and nausea and vomiting (PONV). We also examined the 2 block types for noninferiority. METHODS: A total of 225 patients were propensity matched on 5 potential confounders among 3 study groups (75 per group): (1) pectoralis; (2) serratus; and (3) control. The propensity-matched cohort was used to evaluate the effect of the study group on postoperative in-hospital oral morphine equivalent consumption and PONV. We considered pectoralis noninferior to serratus block if it was noninferior for both outcomes, within 10 mg morphine and 17.5% in PONV incidence margins. Other outcomes included intraoperative fentanyl requirements, pain scores, time to first analgesic request, and duration of recovery room stay. RESULTS: Both pectoralis and serratus blocks were each associated with reduced postoperative in-hospital opioid consumption and PONV compared with control. Pectoralis was noninferior to serratus block for these 2 outcomes. Pectoralis and serratus blocks were each associated with reduced intraoperative fentanyl requirements, prolonged time to first analgesic request, and expedited recovery room discharge compared with control; there were no differences for the remaining outcomes. CONCLUSIONS: Pectoralis and serratus blocks were each associated with a reduction in postoperative in-hospital opioid consumption and PONV compared with conventional opioid-based analgesia after ambulatory breast cancer surgery. Abstract : Published ahead of print March 21, 2017.